(untitled) (Research, Society and Development, 2022)
Introduction: Anxiety is an emotional condition of physical and psychological discomfort, and has become a common disorder of university students. However, studies report that a good level of physical activity can reduce levels of anxiety. Objective: Analyze the correlation between the level of physical activity and the anxiety index of university students in the field of health, female and who are attending the last year of graduation at a certain higher education institution of Teresina-PI. Methodology: IPAQ, BAI and Sociodemographic questionnaires were applied, using forms applied by the Google forms platform, by 56 university students enrolled in the last year of the courses: Medicine, Nursing, Nutrition, Dentistry, Biomedicine, Physiotherapy and Physical Education. Results: According to the IPAQ, 63% of the sample were classified as active or very active, of these 69% had anxiety rates from minimal to light. Conclusion: with the results it wasn’t possible to verify that the high level of physical activity can cause lower levels of anxiety.